The Syntax Characteristics of Advertising Text: Theoretical Aspect (Linguostylistic Studies, 2016)
The article reveals the main trends in modern research of advertising text syntax. The study of this aspect of advertising text has been done on the materials from Ukrainian and foreign sources. The emphasis is laid on the comprehensive analysis of researches dealing with the issues of the Ukrainian advertisement text peculiarities. The problem of syntactic organization of advertising texts is considered in correlation with the other linguistic issues of Ukrainian advertising discourse. Key words: syntax of advertising, function of advertising, text advertising, sentence. References